2022
DOI: 10.3389/fphar.2022.832590
|View full text |Cite
|
Sign up to set email alerts
|

Shuangxinfang Prevents S100A9-Induced Macrophage/Microglial Inflammation to Improve Cardiac Function and Depression-Like Behavior in Rats After Acute Myocardial Infarction

Abstract: Background: Depression is a common complication of cardiovascular disease, which deteriorates cardiac function. Shuangxinfang (psycho-cardiology formula, PCF) was reported to alleviate myocardial ischemia injury and improve depression-like behavior. Interestingly, our previous proteomics study predicted that the protein S100A9 appeared as an important target, and macrophage/microglial inflammation might be involved in the process of PCF improving depression induced by acute myocardial infarction (AMI). This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…LMNA (lamin A/C) [676], VCAM1 [986], PHGDH (phosphoglycerate dehydrogenase) [1100], S100A9 [1045], FKBP5 [1046], FHL2 [1003], ATF3 [85] and MPO (myeloperoxidase) [1084] plays an important role in the development of obesity. LMNA (lamin A/C) [1127], VCAM1 [1110], S100A9 [239], TP63 [1125], JUND (JunD proto-oncogene, AP-1 transcription factor subunit) [1118], FHL2 [1132], ATF3 [93], BPI (bactericidal permeability increasing protein) [1178], DYSF (dysferlin) [1180], MPO (myeloperoxidase) [1195] and ALPL (alkaline phosphatase, biomineralization associated) [1194] were reported to be associated with the prognosis of heart problems. LMNA (lamin A/C) [1313], VCAM1 [1299], PHGDH (phosphoglycerate dehydrogenase) [1382], S100A9 [81], TP63 [1312], FHL2 [1318], ATF3 [80] and MPO (myeloperoxidase) [1375] have been identified as a key genes in idiopathic pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…LMNA (lamin A/C) [676], VCAM1 [986], PHGDH (phosphoglycerate dehydrogenase) [1100], S100A9 [1045], FKBP5 [1046], FHL2 [1003], ATF3 [85] and MPO (myeloperoxidase) [1084] plays an important role in the development of obesity. LMNA (lamin A/C) [1127], VCAM1 [1110], S100A9 [239], TP63 [1125], JUND (JunD proto-oncogene, AP-1 transcription factor subunit) [1118], FHL2 [1132], ATF3 [93], BPI (bactericidal permeability increasing protein) [1178], DYSF (dysferlin) [1180], MPO (myeloperoxidase) [1195] and ALPL (alkaline phosphatase, biomineralization associated) [1194] were reported to be associated with the prognosis of heart problems. LMNA (lamin A/C) [1313], VCAM1 [1299], PHGDH (phosphoglycerate dehydrogenase) [1382], S100A9 [81], TP63 [1312], FHL2 [1318], ATF3 [80] and MPO (myeloperoxidase) [1375] have been identified as a key genes in idiopathic pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is associated with the impairment of the epidermal barrier in specific dermatitis, suggesting that S100A9 may be a potential target for treating specific dermatitis(Zhao et al, 2020). S100A9 is also considered a novel and effective regulator of brain inflammation because it can mediate inflammation in microglia/macrophages, ultimately leading to MDD(Sun et al, 2022). These results suggest that as an inducer of inflammation, S100A9 can participate in the pathogenic mechanisms of both AD and MDD.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that ITGAM is a key immune-related gene, which is significantly increased in blood samples of patients with AMI ( 25 ). S100A9 and S100A12 are up-regulated in the process of AMI and can induce macrophage/microglia inflammation ( 26 , 27 ). Shuangxinfang (psycho-cardiology formula, PCF) could inhibit this process and improve the heart function of mice with myocardial infarction ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…S100A9 and S100A12 are up-regulated in the process of AMI and can induce macrophage/microglia inflammation ( 26 , 27 ). Shuangxinfang (psycho-cardiology formula, PCF) could inhibit this process and improve the heart function of mice with myocardial infarction ( 26 ). TREM-1 is a receptor of immunoglobulin superfamily, which has been proved to induce and amplify inflammation in the progress of acute and chronic diseases ( 28 ).…”
Section: Discussionmentioning
confidence: 99%